A dictionary of nursing - Martin, E. A. (Elizabeth A.), 1945- .); McFerran, Tanya A. (Oxford : Oxford University Press, 2008)
The new editions of these best-selling and trusted dictionaries have been fully updated and revised to take account of recent developments in nursing practice and related fields
At head of title: Ideal reference for nursing students and practising nurses
13
Keywords: Nursing -- Dictionaries